New Horizons in Treatment of Knee Osteoarthritis: A Brief Look-up at Emerging Approaches - Zare, Afsaneh; Iraji, Aida; Zare, Shahrokh; Koohi-Hosseinabadi, Omid; Bagheri, Fateme; Tanideh, Romina; Tanideh, Nader (West Kazakhstan Medical Journal, 2023)
Knee osteoarthritis (OA) is a chronic and prevalent musculoskeletal condition that is the underlying cause of disability in most patients worldwide. Even though the pathophysiology of KOA has not yet been fully understood and includes a wide range of risk factors, current therapeutic options are temporarily palliative rather than curative. In recent years, new strategies have focused on the curative agents. As part of this review, we highlight the latest treatment approaches for KOA.